Novel flame retardant thermoset resin blends derived from a free-radically cured vinylbenzylated phenolic novolac and an unsaturated polyester for marine composites. (May 2016) - Kandola, Baljinder K.; Ebdon, John R.; Luangtriratana, Piyanuch; Krishnan, Latha
Abstract: A phenolic novolac resin has been chemically reacted with 4-vinylbenzyl chloride to introduce polymerizable vinyl benzyl groups. The modified novolac spontaneously polymerizes like styrene, is physically and chemically compatible with a typical unsaturated polyester (UP) resin, and can be free-radically cured (crosslinked) alone and in mixtures with UP using styrene as a reactive diluent. The cured vinylbenzylated novolac and co-cured blends of it with UP show superior flame retardance to cured UP alone and have potential applications as matrix resins in glass-reinforced composite laminates especially for marine structures.